Point blank : an Alex Rider adventure - Horowitz, Anthony, 1955- (New York : Speak, 2004)
Fourteen-year-old Alex continues his work as a spy for the British MI6, investigating an exclusive school for boys in the French Alps.
Sequel to: Stormbreaker.
Includes preview chapter from: Skeleton Key.
Keywords: Espionage -- Juvenile fiction; Orphans -- Juvenile fiction; Cloning -- Juvenile fiction; Spies -- Fiction; Cloning -- Fiction; Schools -- Fiction; Orphans -- Fiction